POLITICAL COMMUNICATION STRATEGY OF THE PDI PERJUANGAN PARTY - Nadia Zuhra Karla Lubis; Rosita Anggraini Tagor (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
Political communication strategy determines the victory of political parties in getting the highest position. The results of the 2019 election, showed that the PDI-P was the winning political party with a total of 27,053,961 votes or around (19.33%) of the vote. The study aims to explore the political communication strategy carried out by the PDI-P party to win the sympathy of voters so that it wins political contestation. . The literature review in this study focuses on political communication and political communication strategies. This study uses descriptive qualitative research methods with depth interview techniques to informants. The results of this study show the political communication strategies of the PDI party, including: 1) by utilizing the power of the mass media to compete in the 2019 elections such as electronic media 2) the consistent design of political messages that are often conveyed such as to always work for the interests and welfare of the people, our work is Indonesian work and 3) the strategy of forming and maintaining a brand image as a political party that favors the small people with the association of the parties “wong cilik”.